Effect of Sex , Sexual Maturity and Season on the Chemical Composition of Golden Gray Mullet Chelon auratus (Risso, 1810) Caught from the Marine Water of Lattakia Governorate (Syria). - أديب سعد; إبراهيم نيصافي; عيسى بركات (Latakia University Journal -Biological Sciences Series, 2022)
The effects of seasonal and sexual differences on the chemical composition of the gold gray mullet fish species C. auratus caught from the marine waters of Lattakia Governorate were investigated. Moisture, crude protein, crude fat and ash were determinated as a percentage of the muscles of the caught fish. The results revealed that the autumn season was the highest in terms of nutritional components (protein 22.02%, fat 10.58%, ash 2.38%), while the summer season was the lowest (protein 20.56%, fat 4.68%, ash 1.72%). The results also showed the superiority of females in the values of the nutritional components over males, where the values were for females (protein 21.54%, fat 7.9%) and males (protein 21.12%, fat 7.3%), while the ash values did not show significant differences between males and females